Evropski pravi kostanj - Castanea sativa Mill. - Jurc, Maja (Gozdarski vestnik, 2009)
We present oriental chestnut gall wasp Dryocosmus kuriphilus, a new invasive Asian species of gall wasp on sweet chestnut (Castanea sativa), which was imported in 2004 on the chestnut plants from Piedmont in Italy into Slovenia. Short description of its quarantine status, geographical range of oriental chestnut gall wasp in the world and in Slovenia, morphology, bionomy, description of damages (on young twigs, on the midrib of the leaves and on thespiked male flowers), possible misidentifications, hosts, its most important natural enemies and threat for the stands of sweet chestnut in Slovenia are given. D. kuriphilus is established in our country and in 2009 foresters are registering its spread in the stands of C. sativa in Primorska region. Short description of regulations concerning presented species and measures to reduce its spread speed are also presented. It is supposed that its spread is impossible to stop and that biological suppression with its parasites is the only promising method to prevent serious damages of sweet chestnut stands and orchards in Slovenia.
Keywords: kostanjeva šiškarica; Dryocosmus kuriphilus; pravi kostanj; Castanea sativa; varstvo gozdov; Slovenia; Slovenija